AIDS and Drug Pricing: In Search of a Policy - Steven R. Salbu (Washington University Law Quarterly, 1993)
This Article presents a comprehensive analysis of the policy considerations regarding the pricing of new AIDS drugs. Part I discusses the two countervailing interests that dominate the debate: the effect of patent monopoly policy on the speed and extent of research and development initiatives and the effect of monopoly pricing on drug accessibility. Part II addresses legal, economic, and ethical concerns that are crucial to the formulation of a sound drug pricing policy, including the principles of monopoly theory, the relationship between monopoly and regulation, the proper allocation of price concessions that reduce profits from normal monopoly levels, and the determination of how much profit is necessary to optimize research and development efforts. Part III examines a "negotiated drug pricing" proposal, aimed at creating and maintaining a fair, effective, and efficient response to the AIDS crisis. Part IV contains concluding remarks and suggests further areas of research and inquiry helpful to the thoughtful resolution of the public policy challenges raised herein.
Keywords: AIDS (Disease); Prices; Food drug & amp; cosmetic law & amp; legislation